10 000 Consecutive off Pump Coronary Artery Bypass Grafting Operations Performed in a Single Cardiac Surgery Clinic - A. V. Rudenko; V. I. Ursulenko; A. V. Kupchynskiy; S. P. Spysarenko; T. A. Malysheva (Ukrainian Journal of Cardiovascular Surgery, 2016)
The work summarizes the results of more than 10 000 consecutive off pump coronary artery bypass grafting operations performed in a single cardiac surgery center. The immediate results of these operations, the causes of postoperative complications were analyzed on extensive statistical material.